PENGARUH PENGENDALIAN INTERN KAS TERHADAP EFEKTIVITAS PENGELOLAAN KAS PADA PDAM TIRTA MALEO KABUPATEN POHUWATO - Syamsuddin Syamsuddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
Internal control is a technique that controls the overall supervision of the company's operations, both on the organization or system, or in ways that used to run the company and also the tools that companies use. The good control, no guarantee it will not happen errors and irregularities in the company, but at least will reduce the occurrence of errors and fraud within the limits of the feasible. internal control not only check the correctness of the figures and protect wealth in terms of accounting firms, but also pay attention to the company's organizational structure, improve work efficiency and to analyze how far the implementation of policies that have been outlined by the leadership of the company has done well. An internal control should always be monitored and evaluated so that the benefits of internal control is always accountable